2003
DOI: 10.1046/j.1365-2222.2003.01797.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergen‐mediated modulation of CD23 expression is interferon‐γ and interleukin‐10 dependent in allergic and non‐allergic individuals

Abstract: These data indicate that early immunological effects like down-regulation of CD23 on B cells and monocytes, which are observed during SIT are dose dependent, mediated by IFN-gamma and IL-10 and seem not to depend per se on the sensitization state of an individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Since IFN-has been reported to inhibit the synthesis of IgE and the differentiation of precursor cells to Th2 cells, an increased level of IFNhas been used to explain the anti-asthmatic effect of therapeutic agents. 13,14) We have demonstrated in the present study that IFE reduced Th2 cytokine production (IL-4, IL-5, and IL-13) in cultured splenocytes, whereas it did not increase IFN-production in cultured splenocytes when compared with the OVA-induced mice (Fig. 4).…”
Section: Discussionsupporting
confidence: 50%
“…Since IFN-has been reported to inhibit the synthesis of IgE and the differentiation of precursor cells to Th2 cells, an increased level of IFNhas been used to explain the anti-asthmatic effect of therapeutic agents. 13,14) We have demonstrated in the present study that IFE reduced Th2 cytokine production (IL-4, IL-5, and IL-13) in cultured splenocytes, whereas it did not increase IFN-production in cultured splenocytes when compared with the OVA-induced mice (Fig. 4).…”
Section: Discussionsupporting
confidence: 50%
“…Since IFN-g has been reported to inhibit the synthesis of IgE and the differentiation of precursor cells to Th2 cells, increased level of IFN-g has been used to explain the anti-asthmatic effects of therapeutic agents. 15,16) However, other data have suggested that IFN-g contribute to the activation of eosinophils and thus be likely to augment inflammation. 6,7) Thus it seems to be reasonable that unnecessary immune response caused by Th1 cells as well as inflammation mediated by Th2 cells and eosinophils should be suppressed to treat asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggest that IL‐10 secreting and Foxp3 + regulatory CD4 + T cells, generated during specific immunotherapy or naturally by repeated high‐dose antigen application, e.g. bee stings, mediate an IgG4‐dominated B cell response and tolerance towards allergens [2, 4–9]. T regulatory cells participate in suppression of antigen‐presenting cells which support the generation of effector Th2 and Th1 cells, inhibit the induction of allergen‐specific IgE and induce IgG4 and/or IgA [10].…”
Section: Introductionmentioning
confidence: 99%